Origin of the beta S-globin gene in blacks: the contribution of recurrent mutation or gene conversion or both. - Antonarakis, S E (1984)
In order to investigate the origin(s) of the mutation(s) leading to the beta S-globin gene in North American populations of African ancestry, we analyzed DNA polymorphisms in the beta-globin gene cluster in a large number of both beta A- and beta S-globin gene-bearing chromosomes in U.S. and Jamaican Blacks. We found 16 different haplotypes of polymorphic sites associated with 170 beta S-globin gene-bearing chromosomes. The three most common beta S haplotypes, which account for 151/170 of the beta S-globin gene-bearing chromosomes, are only rarely seen in the chromosomes bearing the beta A-globin gene in these populations (6/47). Two observations suggest multiple origins or interallelic gene conversion, or both, of the beta S mutation. First, the mutation is present in all three beta-globin gene frameworks. Second, the beta S haplotypes can be divided into four groups, each of which cannot be derived from any other by less than two crossing-over events. In summary, our observation of the beta S mutation on 16 different haplotypes in African populations can be best explained by (i) a number of simple recombination events 5' to the beta-globin gene and (ii) up to four independent mutations and/or interallelic gene conversions.